The Development of a Unified Enantioselective, Convergent Synthetic Approach Toward the Furanobutenolide-Derived Polycyclic Norcembranoid Diterpenes: Asymmetric Formation of the Polycyclic Norditerpenoid Carbocyclic Core by Tandem Annulation Cascade - Craig, Robert A. (J Org Chem, 2018)
An enantioselective and diastereoselective approach toward the synthesis of the tetracyclic scaffold of the furanobutenolide-derived polycyclic norditerpenoids is described. Focusing on synthetic efforts toward ineleganolide, the synthetic approach utilizes a palladium-catalyzed enantioselective allylic alkylation for the construction of the requisite chiral tertiary ether. A diastereoselective cyclopropanation–Cope rearrangement cascade enabled the convergent assembly of the ineleganolide [6,7,5,5]-tetracyclic scaffold. Investigation of substrates for this critical tandem annulation process is discussed along with synthetic manipulations of the [6,7,5,5]-tetracyclic scaffold and the attempted interconversion of the [6,7,5,5]-tetracyclic scaffold of ineleganolide to the isomeric [7,6,5,5]-core of scabrolide A and its naturally occurring isomers. Computational evaluation of ground state energies of late-stage synthetic intermediates was used to guide synthetic development and aid in the investigation of the conformational rigidity of these highly constrained and compact polycyclic structures.